Cocaine modulates locomotion behavior in C. elegans. - Alex Ward; Vyvyca J Walker; Zhaoyang Feng; X Z Shawn Xu (PLoS ONE)
Cocaine, a potent addictive substance, is an inhibitor of monoamine transporters, including DAT (dopamine transporter), SERT (serotonin transporter) and NET (norepinephrine transporter). Cocaine administration induces complex behavioral alterations in mammals, but the underlying mechanisms are not well understood. Here, we tested the effect of cocaine on C. elegans behavior. We show for the first time that acute cocaine treatment evokes changes in C. elegans locomotor activity. Interestingly, the neurotransmitter serotonin, rather than dopamine, is required for cocaine response in C. elegans. The C. elegans SERT MOD-5 is essential for the effect of cocaine, consistent with the role of cocaine in targeting monoamine transporters. We further show that the behavioral response to cocaine is primarily mediated by the ionotropic serotonin receptor MOD-1. Thus, cocaine modulates locomotion behavior in C. elegans primarily by impinging on its serotoninergic system.